PENGARUH POLA ASUH ORANG TUA TERHADAP KECERDASAN SPIRITUAL ANAK DI LINGKUNGAN ST. YOHANES PEMANDI PAROKI ST.FRANSISKUS DE SALES - Tokan, Sesilia Dali; Tukan, Antonius I. N. (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2023)
The reason this research was conducted was to examine parental parenting patterns and their impact on the spiritual intelligence of children in the St. John the Bath. The method used in this research is a qualitative method with a description approach. The data analysis technique in this qualitative research is using data collection, data reduction, and display and data verifying techniques. The research results show that parents in the St. Yohanes Pemandi has not provided a good parenting style to the children. For this reason, parents need to make the home the first place for spiritual education so that children can grow in their spiritual life in the family and have an influence on other people in life in society.